Recent national trends in Salvia divinorum use and substance-use disorders among recent and former Salvia divinorum users compared with nonusers - Blazer DG; Li JH; Yang C; Woody GE; Wu LT (Dove Medical Press, 2011)
Li-Tzy Wu1, George E Woody2, Chongming Yang3, Jih-Heng Li4, Dan G Blazer11Department of Psychiatry and Behavioral Sciences, Duke University Medical Center, Durham, NC, USA; 2Department of Psychiatry, University of Pennsylvania and Treatment Research Institute, Philadelphia, PA, USA; 3Social Science Research Institute, Duke University, Durham, NC, USA; 4College of Pharmacy, Kaohsiung Medical University, Kaohsiung, TaiwanContext: Media and scientific reports have indicated an increase in recreational use of Salvia divinorum. Epidemiological data are lacking on the trends, prevalence, and correlates of S. divinorum use in large representative samples, as well as the extent of substance use and mental health problems among S. divinorum users.Objective: To examine the national trend in prevalence of S. divinorum use and to identify sociodemographic, behavioral, mental health, and substance-use profiles of recent (past-year) and former users of S. divinorum.Design: Analyses of public-use data files from the 2006–2008 United States National Surveys on Drug Use and Health (N = 166,453).Setting: Noninstitutionalized individuals aged 12 years or older were interviewed in their places of residence.Main measures: Substance use, S. divinorum, self-reported substance use disorders, criminality, depression, and mental health treatment were assessed by standardized survey questions administered by the audio computer-assisted self-interviewing method.Results: Among survey respondents, lifetime prevalence of S. divinorum use had increased from 0.7% in 2006 to 1.3% in 2008 (an 83% increase). S. divinorum use was associated with ages 18–25 years, male gender, white or multiple race, residence of large metropolitan areas, arrests for criminal activities, and depression. S. divinorum use was particularly common among recent drug users, including users of lysergic acid diethylamide (53.7%), ecstasy (30.1%), heroin (24.2%), phencyclidine (22.4%), and cocaine (17.5%). Adjusted multinomial logistic analyses indicated polydrug use as the strongest determinant for recent and former S. divinorum use. An estimated 43.0% of past-year S. divinorum users and 28.9% of former S. divinorum users had an illicit or nonmedical drug-use disorder compared with 2.5% of nonusers. Adjusted logistic regression analyses showed that recent and former S. divinorum users had greater odds of having past-year depression and a substance-use disorder (alcohol or drugs) than past-year alcohol or drug users who did not use S. divinorum.Conclusion: S. divinorum use is prevalent among recent or active drug users who have used other hallucinogens or stimulants. The high prevalence of substance use disorders among recent S. divinorum users emphasizes the need to study health risks of drug interactions.Keywords: alcohol-use disorders, drug-use disorders, ecstasy, lysergic acid diethylamide, major depression, multiple race, nicotine dependence, phencyclidine, prescription drug abuse